Relationship Between Pneumonia and Dysphagia in Patients With Multiple System Atrophy - Wada, Ayako; Kawakami, Michiyuki; Yamada, Yuka; Kaji, Kentaro; Hijikata, Nanako; Liu, Fumio; Otsuka, Tomoyoshi; Tsuji, Tetsuya (Frontiers in Neurology, 2022)
Introduction: Dysphagia is one of the most clinically significant disabilities in patients with multiple system atrophy (MSA), because it can cause aspiration pneumonia, which is potentially fatal. In this study, the Neuromuscular disease Swallowing Status Scale (NdSSS), which was developed to evaluate dysphagia in patients with neuromuscular diseases, was evaluated in patients with MSA. In addition, the correlation between a history of pneumonia and swallowing function was evaluated. Methods: Study 1: Reliability, concurrent validity, and responsiveness of the NdSSS in patients with MSA. In 81 patients NdSSS was tested for its interrater and intrarater reliability using weighted kappa statistics. The concurrent validity was assessed by correlating the NdSSS with existing scales (Functional Oral Intake Scale, Functional Intake LEVEL Scale, and the unified MSA rating scale (UMSARS)) and with videofluorographic swallowing assessments, using Spearman’s rank correlation coefficients. Additionally, scale responsiveness was determined using the standardized response mean in 23 patients. Study 2: Cross-sectional survey of swallowing function and history of pneumonia. Data of a history of pneumonia, UMSARS, NdSSS, age, sex, MSA subtype, and disease duration were retrospectively obtained from the medical records of 113 patients with MSA. Differences in these parameters and NdSSS scores between those with and without a history of pneumonia were examined using the Mann-Whitney test or chi-squared test. Furthermore, clinical factors related to a history of pneumonia were examined by binomial logistic regression analysis. Results: The NdSSS showed satisfactory reliability, concurrent validity, and responsiveness. A history of pneumonia was related to the severity of MSA, age, MSA subtype, and NdSSS stage. Binomial logistic regression analysis showed that the NdSSS stage (odds ratio (OR), 0.490; 95% confidence interval (CI), 0.301-0.797, p=0.001) and MSA subtype (OR, 4.031; 95% CI, 1.225-13.269, p=0.021) were significantly associated with a history of pneumonia. Conclusions: In patients with MSA, the NdSSS has sufficient reliability, concurrent validity, and responsiveness for assessing dysphagia. Patients with a history of pneumonia have more severe dysphagia. We found that the pneumonia risk was related to NdSSS stage and MSA-p (predominantly parkinsonism). Meticulous care to prevent aspiration is needed from early stages of the disease.